PYGMALIONIZATION: DO ACTION FIGURES, NENDOROIDS, AND PLUSHIES OF FILMS AND GAMES TELL A STORY? - Prakoso, Mohammad Romdhoni; Yanuasari, Rizki Adi; Purnama, SF Lukfianka Sanjaya; Prihastiwi, Lusiana (CrossOver Journal of Adaptation Studies, 2023)
Studies on merchandise or merch as paratexts that serve as nano-narratives in adaptation context are under investigated. We argue that treating merchandise of hyped films and games as in the mentioned fashion might disclose a novel perspective in perceiving them as a narrative text. Employing the theories of paratextuality by Genette, ergodic literature by Aarseth, ludic adaptation by Purnomo et al., franchising storytelling by Parody and nano-narratives by Petten on a corpus of merch from forty animated films and games, we proposed a neologism that we dubbed pygmalionization. This perspective refers to adapting animated films and games into toy-based merch e.g. action figures, nendoroids, and plushies and treating them as paratexts with the purposes of serving nano narratives and of extending the narrative experiences methectically and metathectically to the general audiences and fans through transtylization. This study is expected to provide insights for adapted merchandise makers and scholars in regard to treating the merchandise as a paratext with nano-narrative functions.